Jabatan Kerja Raya Daerah Segamat, Johor / Fatin Hamimi Saiful Amri - Saiful Amri, Fatin Hamimi (UiTM Johor Cawangan Kampus Pasir Gudang, 2018)
This report is set oul to give the reader full information about my industrial training in Jabatan Kerja Raya (JKR) Segamat, Johor. Industrial taining is one ef the compulsory curriculums in Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang which students need to complete whether in consultant, construction or Government Company. This course is sets up for student in order to give them experience and gain knowledge in working environment before going through the real working life. My industrial training is at Jabatan Kerja Raya or known as JKR which provide maintenance and construction to the public sectors in Malaysia. In Jabatan Kerja Raya, I have been send to Facilities Department and Road Department. At this branched, I have been assigned to a lot of site project such as repairing works, installation works, regulate and resurface road works. To sum up, I had learnt on the road treatment, sequences and method to repair the road which is the CIPR treatment. During my placement, I have learned a lot new knowledge about road maintenance and safety. These knowledge are useful for me in future and gives me a lot of advantageous to prepare myself for my future career. Last but not least, in this report included the introduction, brief background about this company, task, recommendations and conclusion in details.